SIRT6 inhibits proliferation and invasion in osteosarcoma cells by targeting N-cadherin - Gao, Yi (Oncol Lett, 2019)
SIRT6, is a member of the NAD-dependent sirtuin family of enzymes, and has been reported as a novel tumor suppressor gene or oncogene, dependent on the type of cancer. However, the role of SIRT6 in osteosarcoma has not been investigated. The present study demonstrated that the expression of SIRT6 was downregulated in osteosarcoma tissues and osteosarcoma cell lines when compared with adjacent tissues or osteoblastic cell lines. Kaplan-Meier analysis was performed to evaluate the prognostic significance of SIRT6. The overall survival of patients with higher expression of SIRT6 was significantly longer than patients with lower expression. Subsequently, MTT and invasion assays were performed to detect the biological functions of SIRT6 in osteosarcoma cells in vitro. The results revealed that overexpression of SIRT6 inhibited SAOS-2 and MG-63 cell proliferation and invasion. Knockdown of SIRT6 enhanced cell ability for the proliferation and invasion. A qChIP assay, luciferase reporter assay, reverse transcription-quantitative polymerase chain reaction and western blotting confirmed that CDH2 (N-cadherin) was a target of SIRT6. SIRT6 overexpression suppressed N-cadherin on the mRNA and protein levels. In addition, it was confirmed that the promotional effect of Si-SIRT6 on OS cell growth and invasion was suppressed by downregulating N-cadherin. The present study suggested that SIRT6 may serve as a tumor suppressor during the development of osteosarcoma. In addition, N-cadherin may be a promising therapeutic target for osteosarcoma.